2022
DOI: 10.1007/jhep02(2022)120
|View full text |Cite
|
Sign up to set email alerts
|

Scattering amplitudes of Kaluza-Klein strings and extended massive double-copy

Abstract: We study the scattering amplitudes of massive Kaluza-Klein (KK) states of open and closed bosonic strings under toroidal compactification. We analyze the structure of vertex operators for the KK strings and derive an extended massive KLT-like relation which connects the N-point KK closed-string amplitude to the products of two KK open-string amplitudes at tree level. Taking the low energy field-theory limit of vanishing Regge slope, we derive double-copy construction formula of the N-point massive KK graviton … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…With these in minds, we have further used a first principle approach of the KK string theory in our recent study [39] to derive the extended massive KLT-like relations between the product of the KK open string amplitudes and the KK closed string amplitude. In the field theory limit, we can derive the exact double-copy relations between the product of the KK gauge boson amplitudes and the KK graviton amplitude at tree level [39]. In such exact double-copy relations, all the relevant helicity indices of the external KK gauge boson states are summed over to match the corresponding polarization tensors of the external KK graviton states.…”
Section: Double-copy Construction Of Kk Amplitudesmentioning
confidence: 99%
“…With these in minds, we have further used a first principle approach of the KK string theory in our recent study [39] to derive the extended massive KLT-like relations between the product of the KK open string amplitudes and the KK closed string amplitude. In the field theory limit, we can derive the exact double-copy relations between the product of the KK gauge boson amplitudes and the KK graviton amplitude at tree level [39]. In such exact double-copy relations, all the relevant helicity indices of the external KK gauge boson states are summed over to match the corresponding polarization tensors of the external KK graviton states.…”
Section: Double-copy Construction Of Kk Amplitudesmentioning
confidence: 99%
“…Consistent double-copy constraints for massive mediators is a subject of ongoing study [489], including generalizations to topological massive theories in three dimensions, see e.g. [208,209,424,425,427,489,490] and references therein.…”
Section: Generalizing the Double Copy And The Klt Bootstrapmentioning
confidence: 99%
“…It was for example found that gauge theories with massive (scalar or fermionic) matter in the fundamental representation can also be double-copied [8][9][10][11][12][13][14], and even theories with spontaneous symmetry breaking obey the CK duality [15]. In addition, the double copy of massive gauge bosons has been considered in [16][17][18][19][20]. Besides gauge theories, a double-copy structure has been observed in pure scalar theories such as the aforementioned bi-adjoint scalar theory and the non-linear sigma model [21,22].…”
Section: Jhep05(2022)042 1 Introductionmentioning
confidence: 99%